2008
DOI: 10.1086/524100
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐Separation Binaries Do Not Affect the First Steps of Planet Formation

Abstract: The first steps of planet formation are marked by the growth and crystallization of sub-micrometer-sized dust grains accompanied by dust settling toward the disk midplane. In this paper we explore whether the first steps of planet formation are affected by the presence of medium-separation stellar companions. We selected two large samples of disks around single and binary T Tauri stars in Taurus that are thought to have only a modest age spread of a few Myr. The companions of our binary sample are at projected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…According to Zsom et al (2010), the aggregate sizes are lower in eccentric disks than in axisymmetric disk environments owing to the increase in the relative velocity between the dust particles. We note, however, that an investigation of the SED slopes of medium-separation T Tauri binaries by Pascucci et al (2008) showed that the extent of dust processing in the disk surface layer and the degree of dust settling in binary disks do not differ significantly from those in disks around single stars.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…According to Zsom et al (2010), the aggregate sizes are lower in eccentric disks than in axisymmetric disk environments owing to the increase in the relative velocity between the dust particles. We note, however, that an investigation of the SED slopes of medium-separation T Tauri binaries by Pascucci et al (2008) showed that the extent of dust processing in the disk surface layer and the degree of dust settling in binary disks do not differ significantly from those in disks around single stars.…”
Section: Introductionmentioning
confidence: 58%
“…The binary eccentricity is neglected in this particular calculation. The distance unit is taken to be 40 AU accordingly to the measured separation (Pascucci et al 2008). The initial disk mass is set to 2 × 10 −3 M by the choice of Σ = 17.2 g/cm 2 at 1 AU.…”
Section: Hydrodynamic Disk Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of the three spectroscopic binary (SB) systems, silicate dust is either seen in small amounts or is absent, which can be explained by the removal of dust inside the circumbinary disk. Pascucci et al (2008) demonstrated that companions at separations of tens of AU have no impact on the dust evolution, which would be interesting to study for a carefully defined target sample with closer companions. Table 4.…”
Section: Influence Of Companionsmentioning
confidence: 99%
“…Considering disks located in multiple systems, the properties of their innermost, planet-forming, regions are indistinguishable from those of single stars (e.g., White & Ghez 2001, Pascucci et al 2008. This suggests that the required initial conditions for planet formation are met equally well in the higher-mass component of a multiple system as in single stars, but that lower-mass components may have more adverse initial conditions to form planets.…”
mentioning
confidence: 99%